Transcriptome Profiling of Neovascularized Corneas Reveals miR-204 as a Multi-target Biotherapy Deliverable by rAAVs - Yi Lu (Molecular Therapy: Nucleic Acids, 2018)
Corneal neovascularization (NV) is the major sight-threatening pathology caused by angiogenic stimuli. Current drugs that directly target pro-angiogenic factors to inhibit or reverse the disease require multiple rounds of administration and have limited efficacies. Here, we identify potential anti-angiogenic corneal microRNAs (miRNAs) and demonstrate a framework that employs discovered miRNAs as biotherapies deliverable by recombinant adeno-associated viruses (rAAVs). By querying differentially expressed miRNAs in neovascularized mouse corneas induced by alkali burn, we have revealed 39 miRNAs that are predicted to target more than 5,500 differentially expressed corneal mRNAs. Among these, we selected miR-204 and assessed its efficacy and therapeutic benefit for treating injured corneas. Our results show that delivery of miR-204 by rAAV normalizes multiple novel target genes and biological pathways to attenuate vascularization of injured mouse cornea. Importantly, this gene therapy treatment alternative is efficacious and safe for mitigating corneal NV. Overall, our work demonstrates the discovery of potential therapeutic miRNAs in corneal disorders and their translation into viable treatment alternatives.